The Use of Conditional Sentence in the Short Story “Who Ate the Bread?” - Dzakiyah Darajat; Hanafi Aryunsyah Indarto; Selva Rizky Akmalia; Yani Lubis (Journal of Innovative and Creativity, 2025)
Conditional sentence is one of the important structures in English that expresses cause-and-effect relationship based on certain conditions. This research uses qualitative method with literature study approach and content analysis. Data were collected from short story texts, scientific journals, and online sources, then analyzed descriptively through the identification and classification of conditional sentences. The results show that this short story contains various types of conditional sentences, such as zero, first, second, and third conditional, which play a role in building the storyline, characterizing the characters, and strengthening the moral message. The use of conditional sentences not only enriches the narrative, but also helps readers understand the various possibilities and consequences in the story. This finding confirms the importance of mastering conditional sentences in English language learning, especially in analyzing literary texts.